Concept for Mobility and Interconnections Aspects in Converged NGN-Based IPTV Architecture - Eugen Mikoczy; Radovan Kadlic; Pavol Podhradsky (International Journal of Digital Multimedia Broadcasting)
The progress and evolution trends in the area of ICT and ICT infrastructure based on convergence processes create new opportunities. Service providers and network operators can provide a wide spectrum of multimedia services and applications to end users. The IPTV services represent a specific group of multimedia services which are in the sphere of interest of the telecommunication technical community but also subscribers. Standardization bodies like ETSI TISPAN or ITU-T have defined standards for NGN-based IPTV architecture and services (IMS and non-IMS). The paper evaluates possibilities and potential architecture for concept of converged NGN IPTV. New vision of the converged NGN IPTV architecture is presented together with proposed enhancements compared to IMS-based IPTV where single converged platform can serve fixed, mobile, or wireless terminals. The concept for IPTV service roaming with mobility support and different interconnection scenarios are discussed with intention to show potential user benefits.